PERBANDINGAN DECISION TREE PADA ALGORITMA C 4.5 DAN ID3 DALAM PENGKLASIFIKASIAN INDEKS PRESTASI MAHASISWA (Studi Kasus: Fasilkom Universitas Singaperbangsa Karawang) - Jaenudin, Jejen; Pudjo Widodo, Prabowo (Krea-TIF: Jurnal Teknik Informatika, 2015)
This study applied a data mining model of student’s grade point classification at the department of information technology on computer science faculty singaperbangsa university karawang. The objective of the study is to comprehend the description of rule models which are obtained to produce a decision based on “satisfied and dissatisfied” predicates. The  decision tree algorithm on this study are the C 4.5 and ID3 algorithms. For data analysis, this study uses supporting software of RapidMiner 5.1. In designing data  mining process, this research uses Cross- Industry Standard Process for Data Mining (CRISP-DM) model.    The resulting output is C 4.5 decision tree algorithm might support the computer science faculty of singaperbangsa university karawang on decision-making in teaching and learning process as the basic reference for future improvements.